The Impact of Banking Concentration on Investment and Economic Growth in Jordan - Al-Tanbour, Khalid Najeh; Awad-Warrad, Talib Mohammad (International Journal of Economics and Financial Issues, 2021)
This paper aims to investigate the impact of banking concentration on investment and economic growth for the Jordanian economy. It utilizes annual sample for the period between 1980 and 2018. The study examines the effectiveness of the Structure-Conduct-Performance (SCP) hypothesis and the other Efficient-Structure (ES) hypothesis for the case of Jordan. The Augmented Dickey-Fuller (ADF) and cointegration tests are used and the results indicate to the appropriateness of the following econometric techniques: Autoregressive Distributed Lag Bound test (ARDL), the fully modified OLS (FMOLS) and generalized methods of moments (GMM). The estimation results indicated to negative relationship between concentration index and both investment spending and the rate of real economic growth. The study recommended that the Central Bank of Jordan should continue to allow new banks to enter the banking market to reduce the impact of concentration as much as possible to achieve competitive gains in the Jordanian banking sector. Keywords: Banking Concentration, FMOLS, GMM, Investment, Economic Growth. JEL Classification: G210 DOI: https://doi.org/10.32479/ijefi.10891